al-Muqaranah Baina Natijah Ta’lim ‘Ibr al-Internet wa Ta’lim al-Liqa’i fi Ta’lim al-Lughah al-‘Arabiyyah laday al-Thullab al-Tsanawi - Jazilah, Ela; Abdullah, Ahmad Hafidz (Tanwir Arabiyyah: Arabic as Foreign Language Journal, 2022)
It is no wonder that learning outcome is very important to measure the success of the education activities that are implemented. But how if education that is usually implemented with offline education, is replaced by online education because of the Covid-19 pandemic. Based on that, The objectives of this research are to find out the difference between the result of online education and offline learning in teaching Arabic among students at the Islamic Intermediate School “Darus Sholah”. The methodology of this research is the quantitative approach, and the method of collecting observation and documentation consists of data analysis by descriptive quantitative analysis with induction statistics by type, non-parametric statistics. The results of the research there is no comparison between the result of online education and offline education in teaching Arabic among students at the Islamic Intermediate School “Darus Sholah”. In conclusion, the result of the analysis hypothesis shows that 0.09 has more value than 0.05 (0.05 < 0.09) µ1 = µ2 H0, H0 is accepted and H1 data is rejected. This means that the data showed is accepted.